J/[psi] production as a function of charged-particle pseudorapidity density in p-Pb collisions at √sNN=5.02TeV - Adamová, Dagmar; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (Physics letters, 2018)
We report measurements of the inclusive J/ψ yield and average transverse momentum as a function of charged-particle pseudorapidity density dNch/dη in p-Pb collisions at sNN=5.02TeV with ALICE at the LHC. The observables are normalised to their corresponding averages in non-single diffractive events. An increase of the normalised J/ψ yield with normalised dNch/dη, measured at mid-rapidity, is observed at mid-rapidity and backward rapidity. At forward rapidity, a saturation of the relative yield is observed for high charged-particle multiplicities. The normalised average transverse momentum at forward and backward rapidities increases with multiplicity at low multiplicities and saturates beyond moderate multiplicities. In addition, the forward-to-backward nuclear modification factor ratio is also reported, showing an increasing suppression of J/ψ production at forward rapidity with respect to backward rapidity for increasing charged-particle multiplicity.
Available online 8 November 2017
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
The ALICE Collaboration: A. Adamová, V. Anguelov, M. Arslandok, M.C. Danisch, P. Glässel, J. Kim, S. Klewin, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 09.07.2019